Meritve dimenzij: Praktikum (navodila za vaje pri predmetu Tehniške meritve) - Črepinšek Lipuš, Lucija (University of Maribor Press, 2022)
Practicum (Instructions for Exercises in the Subject Engineering Measurement). Dimension measurement practicum is a study tool for performing laboratory exercises in the subject Engineering measurement. Exercises are intended to learn simple techniques for measuring dimensions in manufacturing engineering. It includes the implementation of various examples of measurements with an emphasis on finding solutions to achieve the lowest possible errors and the best possible measurement reliability. The publication is available only to students of the University of Maribor, Faculty of Mechanical Engineering.